2013
DOI: 10.1159/000354508
|View full text |Cite
|
Sign up to set email alerts
|

The E-F Hand Calcium-Binding Protein S100A4 Regulates the Proliferation, Survival and Differentiation Potential of Human Osteosarcoma Cells

Abstract: This is an Open Access article licensed under the terms of the Creative Commons AttributionNonCommercial 3.0 Unported license (CC BY-NC) (www.karger.com/OA-license), applicable to the online version of the article only. Distribution permitted for non-commercial purposes only. Abstract Background/Aims: Osteosarcoma (OS) is the most common primary bone malignancy in children and young adults. Molecular mechanisms underlying the pathogenesis of OS remain to be fully understood. Several members of the E-F hand cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 65 publications
4
35
0
Order By: Relevance
“…Specifically, we found that IPF MPCs express higher levels of S100A4 compared with control MPCs (14). S100A4, a calcium binding protein, is upregulated in cancer stem cells, where it controls proliferation, differentiation, and metastasis (15)(16)(17)(18)(19)(20)(21)(22). S100A4 also amplifies TGF-β-induced fibroblast activation in the progressive fibrotic disorder systemic sclerosis (23).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Specifically, we found that IPF MPCs express higher levels of S100A4 compared with control MPCs (14). S100A4, a calcium binding protein, is upregulated in cancer stem cells, where it controls proliferation, differentiation, and metastasis (15)(16)(17)(18)(19)(20)(21)(22). S100A4 also amplifies TGF-β-induced fibroblast activation in the progressive fibrotic disorder systemic sclerosis (23).…”
Section: Introductionmentioning
confidence: 83%
“…While important, these studies are beyond the scope of the current body of work. S100A4 has also been termed metastasin because it regulates cancer cell metastasis (15)(16)(17)(18)(19)(20)(21)(22). While S100A4 levels are elevated in both cancer cells and IPF cells, IPF cells do not metastasize, suggesting that there are important differences between cancer and fibrosis in relation to S100A4 function.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed S100A4 to be protective against pro-apoptotic stimuli [96][97][98]. Orre et al [99] showed that S100A4 interacts with the tumor suppressor p53 in the nucleus and promotes p53 degradation.…”
Section: Wnt Signaling Target: S100a4mentioning
confidence: 99%
“…1, significant suppression of S100A4 expression was observed using RT-qPCR and western blotting. S100A4 is important in a variety of cellular events, including cell growth and apoptosis (18,19). However, previous discrepancy studies suggest the effect of S100A4 on cell growth and apoptosis depends on the cell type.…”
Section: Discussionmentioning
confidence: 99%